Sistem Pendukung Keputusan Penerimaan Bantuan Beasiswa Pada Siswa SMK Menggunakan Metode SMART - Nanang Tedi Kurniadi; Karsito Karsito; Alfiyan Alfiyan; Wisnu Dicky Prahara (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2023)
Processing of assessment data for determining acceptance of student scholarships at SMK Lentera Bangsa Karawang is still carried out conventionally, namely curriculum, the principal determines several points of assessment criteria for determining students who are eligible to receive a scholarship program, in determine the criteria still using the form and recapitulated by the staff later it will be calculated manually the entire value of the specified criteria points has been determined so that there is often a loss of archives used to make reports. With these problems, it is necessary to have a student assessment information system so that the data collection and recapitulation of student criteria values can be facilitated staff in recapitulating student grades making student grade reports. The research method used to determine the scholarship decision system this is the SMART Method. The SMART method is the method used to assess actions associated with a comparison of importance weights between factors and comparison of several alternative choices. This method will give the results of the weighting of each alternative choice accordingly with many defined criteria, namely income parents, number of siblings, average grades and status of orphans. Alternative choice with the largest weight, is the alternative choice that becomes a recommendation to be eligible to receive the scholarship program. The result of this research is a decision support system for scholarship recipients already has the ability to provide convenience in staff determine the results of the process of calculating the criteria for scholarship recipients.